Elephantopus-type sesquiterpene lactones from a Vernonanthura species, Vernonanthura nebularum - Pollora, Genaro Cesar (2003)
Aerial parts of Vernonanthura nebularum, an Argentine endemic whose occurrence is limited to a small area in northwestern Argentina, afforded seven new sesquiterpene lactones of a type characteristic of some Elephantopodiinae rather than Vernonanthura of Vernoniinae. Structures were elucidated by high field 1 H-NMR spectrometry. In revising the generic and subtribal classification of neotropical Vernoniae H. Robinson (Robinson, 1994, 1999) established the new genus Vernonanthura as a segregate from Vernonia sensu stricto (Robinson, 1992) and subsequently included within it (Robinson, 1995) Vernonia nebularum Cabrera as Vernonanthura nebularum (Cabr.) H. Robinson (Cabrera, 1978). Earlier chemical studies of Vernonanthura species, frequently under the old Vernonia binomials (Robinson, 1999), had resulted in the isolation of a variety of flavonoids and sesquiterpene lactones similar to or identical with such compounds found in other Vernonieae (Wagner et al., 1972; Mabry et al., 1975; Bohlmann and Zdero, 1977, 1988; Maldonado et al., 1980; Bohlmann et al., 1981a,b, 1983; Jakupovic et al., 1986, 1987a,b; Catala´n et al., 1986, 1988; Stutts, 1988; Bardo´n et al., 1988, 1992; Budesinsky et al., 1994; Borkosky et al., 1997; Bazon et al., 1997; Kotowicz et al., 1998), while in one instance the occurrence of pimarane and kaurane derivatives was reported (Borkosky et al., 1995). We now describe our chemical study of Vernonanthura nebularum, an Argentine endemic whose occurrence is limited to the Sierra de Calilegua within Jujuy province, Argentina.